Use of preoperative FLAIR MRI and ependymal proximity of tumor enhancement as surrogate markers of brain tumor origin. Issue 9 (September 2015) - Smith, Timothy R.; Hulou, M. Maher; Abecassis, Josh; Das, Sunit; Chandler, James P.
Abstract Neural stem cells proliferate in the subventricular zone and give rise to progeny that differentiate and migrate throughout the brain. We aimed to test the hypothesis that glioma behavior and grade may correlate with the identity of the tumor cell of origin. We evaluated three preoperative radiographic features (fluid attenuated inversion recovery [FLAIR] MRI characteristics, tumor proximity to ventricular ependyma, and subependymal representation) as surrogate markers of tumor origin using a retrospective cohort design. The medical records of 228 patients who underwent surgical resection of a glioma from January 2004 to August 2008 were reviewed. Average patient age was 54.5 years (standard deviation [SD] 15.3) with a male predominance (62.9%). World Health Organization glioma grades amongst the cohort were Grade IV (71.6%), Grade III (21.3%) and Grade II (7.1%). Mean survival was 11.2 months (SD 10.5) with a mean follow up of 12.8 months (SD 11.3). Glioma tumor grade was significantly correlated to FLAIR signal proximity to the ependymal surface (p < 0.01) and inversely with proximity of tumor mass to the ependyma (p < 0.01). The mean distance of tumor-associated FLAIR signal from the ependymal surface for glioblastoma multiforme (GBM) was 1.2 mm (SD 3.3) compared to 4.8 (SD 6.5) for anaplastic astrocytomas and 6.6 mm (SD 6.7; p < 0.01) for low grade gliomas. Conversely, the mean distance of the enhancing tumor mass from the ependyma for GBM was 7.3 mm (SD 9.4), Grade III glioma 2.3 mm (SD 4.9), and Grade II glioma 3.8 mm (SD 6.8; p < 0.05). These findings suggest that higher grade gliomas might arise from less differentiated neuroepithelial cells in the subventricular zone that possess greater migratory potential.